2013
DOI: 10.1007/s00280-013-2080-6
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombocytosis and immunohistochemical expression of connexin 43 at diagnosis predict survival in advanced non-small-cell lung cancer treated with cisplatin-based chemotherapy

Abstract: Thrombocytosis and connexin 43 absence may be reliable surrogate markers for the prediction of chemotherapy response and prognosis for patients with advanced NSCLC, and assessment of these factors may identify a population of patients with advanced NSCLC that is likely to have a prolonged life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…Previous studies have indicated that Cx43 is able to sensitize cells to apoptosis in response to chemotherapeutic drugs through GJC (18,28); however, another study reported that the role of Cx43 in chemotherapy-induced apoptosis is independent of GJC function (12). The results of the MTT assay in the current study indicated a role for Cx43 in mediating the apoptosis of CRC cell lines.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies have indicated that Cx43 is able to sensitize cells to apoptosis in response to chemotherapeutic drugs through GJC (18,28); however, another study reported that the role of Cx43 in chemotherapy-induced apoptosis is independent of GJC function (12). The results of the MTT assay in the current study indicated a role for Cx43 in mediating the apoptosis of CRC cell lines.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have demonstrated that connexins, a group of tumor suppressor genes, are potential anti-oncogenic targets for chemotherapy, and the upregulation of connexin expression can increase sensitivity to antitumor drugs in many cancer types (12,13). Connexins form gap junctions, which are important intercellular channels.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly recent studies tracking connexin levels as a cancer prognostic indicator produced a diverse set of outcomes. Over a dozen studies in the last decade correlate high connexin expression with a significantly better prognosis (e.g., Cx43 in prostate 39 , pancreatic 40 , breast 41 , head and neck SCC 42 , non-small-cell lung 43 , and colorectal 44 cancers; and Cx26 in colorectal 45 and intestinal type-gastric 46 cancers). In contrast, more than a dozen studies correlate high connexin expression with a poor prognosis (e.g., Cx43 in oral SCC 47 , esophageal SCC 48 and non-muscle invasive urothelial bladder cancer 49 ; and Cx26 in breast cancer 50,51 , lung SCC 52 , esophageal SCC 53 , colorectal cancer 37 and papillary and follicular thyroid cancer 54 ).…”
Section: Expression and Localizationmentioning
confidence: 99%
“…Studies have shown that Cx43 plays important roles in cancer development, cell proliferation, apoptosis, invasion and metastasis in lung cancer (20)(21)(22)(23)(24)(25)(26). Most importantly, Cx43 is able to sensitize NSCLC cells to CDDP and ionizing radiation (27,28).…”
Section: Introductionmentioning
confidence: 99%